Upaya Penanganan Anak Putus Sekolah Dengan Program Kejar Paket PKBM Di Kelurahan Pucang Sewu - Ailsyah Putri Oktaviani; Adi Soesiantoro (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2023)
This research aims to investigate the actions taken to address children who have dropped out of education in the Pucang Sewu Village, particularly by involving the Community Learning Center (PKBM). This program has been designed to provide educational opportunities for individuals who cannot access or complete formal education. The research method used is a survey to identify children who have dropped out of education in Pucang Sewu Village and to understand the actions taken by the village authorities in addressing this issue. The research findings indicate that the primary reasons children drop out of education in Pucang Sewu Village are parental separation and life situations without parents. From the analysis, it can be concluded that the village authorities have made efforts by providing assistance through the PKBM Program to these children so that they can obtain the necessary qualifications. Therefore, active participation of the village authorities in addressing the issue of out-of-school children is crucial, so that they have the opportunity to obtain the necessary qualifications and subsequently secure decent employment.